Ion release from a composite resin after exposure to different 10% carbamide peroxide bleaching agents (Journal of Applied Oral Science, 2012)
OBJECTIVE: This in vitro study evaluated the influence of two 10% carbamide peroxide bleaching agents - a commercial product (Opalescence PF; Ultradent Products, Inc.) and a bleaching agent prepared in a compounding pharmacy - on the chemical degradation of a light-activated composite resin by determining its release of ions before and after exposure to the agents. MATERIAL AND METHODS: Thirty composite resin (Filtek Z250; 3M/ESPE) samples were divided into three groups: group I (exposed to Opalescence PF commercial bleaching agent), group II (exposed to a compounded bleaching agent) and group III (control - Milli-Q water). After 14 days of exposure, with a protocol of 8 h of daily exposure to the bleaching agents and 16 h of immersion in Milli-Q water, the analysis of ion release was carried out using a HP 8453 spectrophotometer. The values were analyzed statistically by ANOVA, Tukey's test and the paired t-tests. The significance level was set at 5%. RESULTS: After 14 days of the experiment, statistically significant difference was found between group II and groups I and III, with greater ion release from the composite resin in group II. CONCLUSIONS: The compounded bleaching agent had a more aggressive effect on the composite resin after 14 days of exposure than the commercial product and the control (no bleaching).